Upaya Guru dalam Melatih Kemandirian Anak Usia 4-5 Tahun Melalui Metode Bercerita Pada Pos PAUD Tunas Harapan Pucangan Sadang - Susanti, Susanti; Hermawan, Risdianto (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
Children's independence is an attitude that must be instilled from an early age. However, many young children still do not have an independent attitude. This research discusses teachers' efforts to train independence in children aged 4-5 years through the storytelling method. The place of research was carried out at the Tunas Harapan Early Childhood Post. The problems discussed are (1) how teachers try to train children's independence through the storytelling method and (2) supporting and inhibiting factors faced by teachers in training children's independence. This research aims to find out and describe the efforts made by teachers in training children's independence through the storytelling method as well as describing the supporting and inhibiting factors faced by teachers in training children's independence at the Tunas Harapan Early Childhood Post. This type of research is descriptive qualitative research and the data collection methods used are observation, interviews and documentation. For data validity, researchers used triangulation techniques. The research conclusion shows that the use of the storytelling method by teachers at Pos Paud Tunas Harapan is effective in training children's independence. Teachers use the POAC (planning, organizing, actuation, controlling) approach to design stories that teach the values ​​of independence, organize interactive activities, encourage active participation, and evaluate the results. Even though they are faced with challenges such as uncooperative children's behavior and varying family support, teachers' efforts to integrate this method with the habit of independence at school can increase the development of children's independence